NIVEL DE SATISFACCIÓN DE LOS USUARIOS EN EL CENTRO DE SALUD DE LA PARROQUIA ANTONIO SOTOMAYOR DEL CANTÓN VINCES - Caicedo Leon, Ruth Yomira (2019)
The health center of the Antonio Sotomayor Rural Parish corresponds to the basic level of health care and is attached to the Ministry of Public Health of Ecuador, normally serves an eight-hour schedule and belongs to the Palenque - Vinces 12d05 Health District. eleven people who perform their daily tasks in General Medicine, Pediatrics, Obstetrics, Dentistry, Vaccination. The objective of this case study is to determine the factors that directly and indirectly affect the satisfaction of patients at the health center of Antonio Sotomayor and that do not allow the improvement of the quality of life of each of its inhabitants.